Synthesis and Pharmacological Screening of Bio-active Molecule Fluorobenzothiazole Comprising Sulfonamido Imidazolinone Derivatives - SRINIVAS, KORE; SREENIVASA, G.M.; JAYACHANDRAN, E.; SREENIVASA RAO, D. (Asian Journal of Chemistry, 2010)
6-Fluoro-7-substituted-2-[(2'-phenyl-4'-benzylidenyl-5'-oxoimidazolin-1'-ylamino)benzene-p-sulphonamido] (1,3) benzothiazoles have been synthesized and evaluated for anti inflammatory and anthalmintic activity. Structure of these products has been established by IR, 1H NMR data. Significant activities were observed for some members of the series.